MODERN PREREQUISITES OF THE CONCEPT OF CLASS. THE TRANSITION TOWARDS THE CLASS OF WAGE-LABORERS - DOMŞODI, Dana (Studia Universitatis Babeș-Bolyai Philosophia, 2016)
This article discusses the Western modern prerequisites of class, namely, on the one side a presentation of the social forces and political conjectures that have lead to the formation of modern class. On the other a discussion of some of the elements of Modern political philosophy that have served as an apology or theoretical support to the asymmetric social structures determined by the revolution of the mode of production, namely the transition to capitalism. Modern class is the social expression of an abstraction that has the concrete historical determination of being abstract, such as it is built on the basis of abstract labor (the historically determinate feature of labor of being abstract). Our article has the objective of retracing the intricate relation between the origin of capitalism (the positing of its own condition of possibility and the real subjection of this conditions under the regulative idea of capital, of the law of value) and the social and philosophical movement of troupes that made possible the birth of capitalism, more precisely the co-determination of capital and class. The prolegomena of the concept of class can serve as means for a larger reflection on the nature of social composition and the dialectical relations that bind it to the mode of production.